1991
DOI: 10.1007/bf02549730
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the left spermatic vein diameter measured by ultrasound and palpated varicocele and Doppler ultrasound findings

Abstract: Fifty cases admitted to the urological clinics of Turkish State Railways Hospital, Ankara, were examined by scrotal ultrasonography in order to find the relationship between the left spermatic vein diameter measured by ultrasound and palpated varicocele and Doppler ultrasound findings. In the measured 5-6 mm spermatic vein diameters palpable varicocele and venous regurgitation were found in 100%, in the measured 3-4 mm diameters palpable varicocele was found in 50% and venous regurgitation in 64.5%, and in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 13 publications
3
17
0
3
Order By: Relevance
“…2.5, 2.5-3.5 and 1 3.5 mm). Our results are similar to Hoekstra and Witt's [22] study but quite different from those of Metin et al [23] . However, if VD, RFV and palpability are evaluated together, our results also show some difference from those of Hoekstra and Witt [22] who found the prevalence of reflux to be 65% in cases with a VD between 2.5 and 3.5 mm, 54% of which were palpable, and stated that palpability and reflux were not correlated.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…2.5, 2.5-3.5 and 1 3.5 mm). Our results are similar to Hoekstra and Witt's [22] study but quite different from those of Metin et al [23] . However, if VD, RFV and palpability are evaluated together, our results also show some difference from those of Hoekstra and Witt [22] who found the prevalence of reflux to be 65% in cases with a VD between 2.5 and 3.5 mm, 54% of which were palpable, and stated that palpability and reflux were not correlated.…”
Section: Discussionsupporting
confidence: 77%
“…3 mm are nonpalpable, whereas all cases with a VD 1 3.5 mm are palpable. On the other hand, Metin et al [23] found palpable varicocele in all of the patients with a diameter 1 5 mm, in 50% of the patients with a diameter between 3 and 4 mm and in 16% of the patients with a diameter between 1 and 2 mm. In our study population, we found that the percentage of palpable varicocele increased as the VD increased (7.6, 78.6 and 98.3%, respectively, in VD !…”
Section: Discussionmentioning
confidence: 99%
“…Diameter measurements of patients with clinical varicocele yielded no extra information other than imaging and the numeric expression of the pathology. Venous diameters are found to be increased in clinical varicocele, and reflux can easily be shown by CDU most of the time [8,20].…”
Section: Discussionmentioning
confidence: 99%
“…Venous diameters are found to be increased in clinical varicocele, and reflux can easily be shown by CDU most of the time [14, 15]. In our sample, reflux was detected by CDU in all patients with clinical varicocele.…”
Section: Discussionmentioning
confidence: 65%